2015
DOI: 10.1177/1060028015576180
|View full text |Cite
|
Sign up to set email alerts
|

Drug Interactions With Direct-Acting Antivirals for Hepatitis C

Abstract: None of the DAAs are completely free of drug interactions. Awareness and management of drug interactions is critical to optimize outcomes and minimize adverse effects in these patient populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
1
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 37 publications
0
53
1
3
Order By: Relevance
“…This retrospective study builds on a number of smaller studies suggesting that SOF‐based regimens can be used safely and effectively in patients with severe renal dysfunction, including those receiving hemodialysis, those with decompensated cirrhosis, and those who have undergone liver and/or kidney transplant 14, 15…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This retrospective study builds on a number of smaller studies suggesting that SOF‐based regimens can be used safely and effectively in patients with severe renal dysfunction, including those receiving hemodialysis, those with decompensated cirrhosis, and those who have undergone liver and/or kidney transplant 14, 15…”
Section: Discussionmentioning
confidence: 99%
“…Renal insufficiency is common in recipients of liver transplantation and complicates the decision to treat. Although there are HCV regimens in evaluation27 and approved28 for use in patients with an eGFR <30 mL/minute/1.73 m 2 , SOF‐based regimens are often preferred in patients who have undergone liver transplantation due to high efficacy and less potential for drug–drug interactions 15. The study findings are also of particular interest in those with CTP class B or C cirrhosis as only SOF‐based treatment regimens are currently approved by the U.S. Food and Drug Administration in this population.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10] In contrast, primary route of elimination of simeprevir is feces (>90%) and only a negligible proportion (<1%) takes the Renal route. [11][12] Currently, the American Association for the Study of Liver Diseases (AASLD) and Infectious Diseases Society of America (IDSA) guidelines recommend a standard dose (150 mg) of Simeprevir in patients with CKD stage 4; however, there is lack of evidence for regime containing sofosbuvir and simeprevir in CKD stage 5. 13 Though a combination of sofosbuvir and simeprevir (SOF+SMV) has been recommended for treatment of genotype-1 HCV infected patients by AASLD and EASL, 14 the safety and efficacy of this regimen in patients with severe Renal impairment or with GFR<30 ml/min/1.73m 2 is unknown.…”
Section: Efficacy and Safety Of Sofosbuvir With Simeprevir In Hepatitmentioning
confidence: 99%
“…Furthermore, in patients with severe renal insufficiency, sofosbuvir (which is renally eliminated) has not been studied and safety data has not been established. 14 In contrast, ritonavir, ombitasvir, dasabuvir and paritaprevir are all hepatically eliminated. In the RUBY-1 study, these drugs were shown to be safe in 20 patients with an estimated glomerular filtration rate below 30 mL/min and may thus be preferentially prescribed in those with severe renal insufficiency instead of sofosbuvir containing regimens.…”
Section: Discussionmentioning
confidence: 99%